Hepatic and biliary ascariasis - Anup K Das (Journal of Global Infectious Diseases, 2014)
Ascariasis mainly contributes to the global helminthic burden by infesting a large number of children in the tropical countries. Hepato-biliary ascariasis (HBA) is becoming a common entity now than in the past owing to the frequent usage of ultrasonograms and endoscopic diagnostic procedures in the clinical practice. There are a variety of manifestations in HBA and diagnosis depends on a high index of suspicion in endemic areas coupled with subsequent confirmation by sonographic or endoscopic demonstration of the worm. Most of them present with acute abdomen and jaundice. Oriental or recurrent pyogenic cholangiopathy is possibly the result of HBA, commonly encountered in South-East Asian countries. Conservative treatment with anthelminthic agents is used in the majority. Failure to respond to medical therapy usually indicates the need for endoscopic or surgical interventions. Overall, mortality is low and prognosis is good, but many epidemiological and immunological aspects of Ascaris infection are unclear, meaning our understanding the disease and infection still remains incomplete. Therefore, it is difficult to definitely put down a fixed modality of treatment for HBA. This underscores the need for further studies as ascariasis has the potential to adversely affect the national socio-economy by compromising the health of children and adults alike with its sheer number.